Study on Production of Male Peranakan Ettawa Goat Carcasses with Different Natural Feeding - Oktaviana Hamdi; S. Suparman; H. Hastuti (Chalaza Journal of Animal Husbandry, 2019)
Study on the production of male Peranakan Ettawa goat carcasses with different natural feeding.  The purpose of this research is to find out the output of the Peranakan Ettawa male carcasses with mixed natural food. In this study used the Peranakan goat Ettawa males as many as six tails. The research data is analyzed by various print analyses using the complete random plan (RAL), and the measured parameters include cutting weight, carcass weight, and percentage of the carcass.  The rate of cutting weight gained during the research of P1 (100% mulberry) amounted to 10537.50 grams, P2 (50% mulberry, and 50% Gamal) amounting to 10795.00 grams and P3 (100% Gamal) amounting to 12945.00 grams.  The weight of carcasses gained during the research of P1 (100% mulberry) amounted to 4270.00 grams, P2 (50% mulberry, and 50% Gamal) for 4342.50 grams and P3 (100% Gamal) for 5380.00 grams.  The rate of the percentage of carcasses gained during the research of P1 (100% mulberry) of 40.88%, P2 (50% mulberry, and 50% Gamal) amounted to 40.10%, and P3 (100% Gamal) amounted to 41.78%.   Based on the analysis of the prints, the results were derived that the production of an Ettawa Peranakan goat with a different natural feed gave an unreal effect (p 0.05) to the cut weight, weight of carcasses and the percentage of carcasses.